Visualizing large choroidal blood flow by subtraction of the choriocapillaris projection artifacts in swept source optical coherence tomography angiography in normal eyes. Issue 1 (December 2018) - Maruko, Ichiro; Kawano, Taizo; Arakawa, Hisaya; Hasegawa, Taiji; Iida, Tomohiro
Abstract Optical coherence tomography angiography (OCTA) seems not to image the choroidal blood flow pattern in the normal individual because of the OCT light attenuation. Our purpose in the current study was to visualize the large choroidal blood flow pattern after subtraction of the choriocapillaris projection artifact in normal eyes non-invasively by swept source (SS) OCTA. Sixty-one eyes of 45 individuals (19 men, 26 women) without ocular disease were examined by SS-OCTA (AngioPlex Elite 9000, Zeiss, Germany). A 12 × 12 mm macular area was scanned. Subfoveal choroidal thickness (SCT) was measured, and the choroidal blood flow pattern in a slab of 30 µm width at one-half of SCT was analyzed. In examining the choroidal blood flow pattern, a slab that was between 30 to 60 µm posterior to the retinal pigment epithelium, in which the choriocapillaris blood flow was most clearly imaged, was used for the subtraction of the projection artifacts from the choriocapillaris on the stromal area of choroid. The ratio (%) of the choroidal blood flow area in the whole choroidal region was calculated after binarization. Thirty-four eyes of 27 individuals (12 men, 15 women) were also examined by spectral domain OCTA (SD-OCTA). After the subtraction, the middle and large choroidal blood flow were clearly visible in SS-OCTA in all eyes. The mean SCT was 297 ± 61 µm, and the mean ratio of the choroidal blood flow area was 27.3 ± 8.2%, which was significantly correlated with SCT (R = 0.738, P  < 0.01). SD-OCTA did not show the choroidal blood flow pattern. In conclusion, removal of the projection artifacts of choriocapillaris can make the choroidal blood flow visible in SS-OCTA of normal eyes. Because the ratio of choroidal blood flow area was correlated with SCT, the choroidal blood flow might be an important factor related to the choroidal thickness.